The equalizer. Season four [videorecording (DVD)] - Queen Latifah, 1970-; Wilson, Joseph C.; Glass, Adam, 1968-; Hanning, Rob; Gazzam, Joe; Rome, Kim; Kittles, Tory; Goldberg, Adam, 1970-; Lapira, Liza (CBS, 2024)
Golden Globe, Grammy, and Emmy Award winner Queen Latifah is Robyn McCall, an enigmatic woman with a mysterious background who uses her extensive skills as a former CIA operative to help those with nowhere else to turn. McCall presents to most as an average single mom quietly raising her teenage daughter. But to a trusted few, she is the Equalizer, an anonymous guardian angel and defender of the downtrodden.